Oral astringent stimuli alter the enamel pellicle's ultrastructure as revealed by electron microscopy. (August 2017) - Rehage, Melanie; Delius, Judith; Hofmann, Thomas; Hannig, Matthias
Abstract: Objectives: This electron microscopic study aimed at investigating effects of oral astringent stimuli on the enamel pellicle's morphology. Methods: Pellicles were formed in situ within 30 min on bovine enamel slabs, fixed to individuals' upper jaw splints. The pellicle-coated specimens were immersed in vitro in seven diverse astringent solutions and subsequently analyzed by scanning electron microscopy (SEM), energy dispersive X-ray (EDX) spectroscopy, as well as transmission electron microscopy (TEM). Four biocompatible astringents, namely the polyphenol epigallocatechin gallate, the metal salt iron(III) sulfate, the basic protein lysozyme, and the aminopolysaccharide chitosan, were additionally applied in situ . After rinsing the oral cavity with these compounds, the pellicle's ultrastructure was imaged by SEM and TEM, respectively. Untreated pellicle samples served as controls. Results: Exposure to polyphenols and lysozyme induced particularly thicker and electron-denser pellicles in comparison to the control pellicle with similar characteristics in vitro and in situ . In contrast, acidic chitosan and metal salt solutions, respectively, revealed minor pellicle alterations. The incorporation of Fe and Al into the pellicles treated with the corresponding inorganic salts was verified by EDX analysis. Conclusions: Astringent-induced pellicle modifications were for the first time visualized by TEM. The ultrastructural alterations of the dental pellicle may partly explain the tooth-roughening effect caused by oral astringent stimuli. Clinical significance: Astringents might modify the pellicle's protective properties against dental erosion, attrition, as well as bacterial adhesion, and by this means may influence tooth health. The findings may thus be particularly relevant for preventive dentistry.